Rancang Bangun Game Aim Trainer Untuk Pemain Game FPS Menggunakan Game Engine Unity - Giandhani, Mochammad Rizky; Elsen, Rickard (Institut Teknologi Garut, 2025)
First Person Shooter (FPS) games are played from a first-person perspective and primarily focus on the use of weapons and combat ammunition. In both regular FPS games and competitive FPS genres, precise aiming skills and good reflexes are required to overcome obstacles or enemies encountered during gameplay. These aiming and reflex skills can be developed through gameplay; however, several issues may hinder this process. One such issue in competitive FPS games is the presence of disruptive players with negative behavior, which can affect a player’s concentration during aiming practice. To address this, aiming practice can be conducted using a third-party application known as an aim trainer game. An aim trainer game is an application focused on enhancing FPS players’ ability to control the mouse and accurately move the crosshair toward targets. The aim trainer game in this study will be developed using the Unity game engine, a software platform used to create and develop games, applications, simulations, and more. This research aims to design and develop an aim trainer game as a training medium for players who wish to improve their aiming skills. The game will feature two training modes: timed target shooting and accurate target shooting. The development of the aim trainer game will use the Game Development Life Cycle (GDLC) methodology, consisting of the following stages: Initiation, Pre-production, Production, Testing, Beta, and Release. This study is expected to assist players in enhancing their aiming precision and reflexes, contributing to better performance in FPS games.